How Bell Labs Missed the Microchip. - Michael Riordan
During the 1950s and 1960s, Jack A. Morton was vice president of electronic technology at Bell Telephone Laboratories in Murray Hill, NJ. Morton led the company's effort to transform the transistor from a promising research curiosity into a reliable commercial product that eventually revolutionized electronics. Morton was such a strong, intimidating leader that he could make incorrect decisions and remain unchallenged because of his aggressive style. For failing to recognize the potential of microchips and large-scale integration, Morton cost the parent phone company, AT&T, dearly and may have contributed to its eventual dismemberment. His untimely death in 1971 prevented him from witnessing the consequences of his decisions
Keywords: Bell Telephone Laboratories; Device development team; Electronic technology; Large-scale integration; Semiconductor industry; Transistors